2009
DOI: 10.1111/j.1526-100x.2008.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Succession of a Southern Appalachian Mountain Wetland Six Years following Hydrologic and Microtopographic Restoration

Abstract: Microtopography, which is known to play a key role in the structure and function of wetland communities, is receiving increasing attention in wetland restoration projects. One goal of the Tulula Wetlands Mitigation Bank, which was the first large-scale wetland restoration project in the Blue Ridge Province, was to restore the microtopography in a degraded swamp forest-bog complex. This wetland type has become increasingly rare in the southern Appalachians and is characterized by a distinct microtopography of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…The latter specifically affected more than 50% of Greek marshes and estuaries (ZALIDIS et al 1997). Given the ecological importance of wetlands, alongside their over-exploitation, especially in Greece (ZALIDIS et al 1997, GERAKIS and KALBURTJI 1998, SMARDON 2009, it is not surprising that the development of protection and restoration strategies accompanied by appropriate legislation gained importance at both international and national levels (SMARDON 2009). The tight relation between restoration and vegetation succession explains why the latter is widely discussed in the relevant literature (ROOZEN and WESTHOFF 1985, ROSSELL et al 2009, MATTHEWS and ENDRESS 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter specifically affected more than 50% of Greek marshes and estuaries (ZALIDIS et al 1997). Given the ecological importance of wetlands, alongside their over-exploitation, especially in Greece (ZALIDIS et al 1997, GERAKIS and KALBURTJI 1998, SMARDON 2009, it is not surprising that the development of protection and restoration strategies accompanied by appropriate legislation gained importance at both international and national levels (SMARDON 2009). The tight relation between restoration and vegetation succession explains why the latter is widely discussed in the relevant literature (ROOZEN and WESTHOFF 1985, ROSSELL et al 2009, MATTHEWS and ENDRESS 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ecological importance of wetlands, alongside their over-exploitation, especially in Greece (ZALIDIS et al 1997, GERAKIS and KALBURTJI 1998, SMARDON 2009, it is not surprising that the development of protection and restoration strategies accompanied by appropriate legislation gained importance at both international and national levels (SMARDON 2009). The tight relation between restoration and vegetation succession explains why the latter is widely discussed in the relevant literature (ROOZEN and WESTHOFF 1985, ROSSELL et al 2009, MATTHEWS and ENDRESS 2010. Nevertheless, in Greece there is still a considerable lack of experience regarding the successional pattern of wetland vegetation and within this concept, our objective is to analyze the vegetation succession after 12 years of land use abandonment (agriculture and grazing) using a case study approach in the estuaries of the River Aliakmon, N. Greece.…”
Section: Introductionmentioning
confidence: 99%
“…๋‚ด ๋ถ€ ์ง€์—ญ์€ ์Šต์œค์ง€์„ฑ ์‹์ƒ์ด ์šฐ์ ํ•˜์—ฌ ํ˜„ ์ƒํƒœ๋ฅผ ์œ ์ง€ํ•˜๊ฒ ์œผ๋‚˜ ์ง„ํผ ๋ฆฌ์ƒˆ์™€ ์ฐธ์–ต์ƒˆ๊ฐ€ ๊ฒฝ์Ÿํ•˜๋Š” ์ง€์—ญ์€ ํ–ฅํ›„ ์Šต์œค์ง€์„ฑ์—์„œ ๊ฑด์กฐ์ง€์„ฑ์œผ ๋กœ ์ฒœ์ด๋  ๊ฐ€๋Šฅ์„ฑ์ด ๋†’์€ ์ง€์—ญ์ด๋ฏ€๋กœ ์ˆ˜๊ณ„ ๊ด€๋ฆฌ๋ฅผ ํ†ตํ•œ ์ง€ํ•˜์ˆ˜์œ„ ์œ ์ง€๊ฐ€ ํ•„์š”ํ•œ ๊ฒƒ์œผ๋กœ ์‚ฌ๋ฃŒ๋˜์—ˆ๋‹ค. ํ•œํŽธ, ์‹์ƒ์œ ํ˜•์€ ๋ฌผ์˜ ์†์„ฑ๋ณ€ ํ™”, ์ดํƒ„ ํ‘œ๋ฉด์˜ ์œ ํ˜•, ๋ฌผ ํ๋ฆ„์˜ ๊ฒฝ๋กœ(Heinselman, 1970)์™€ ๋ฏธ์„ธ ์ง€ํ˜•์— ๋”ฐ๋ผ ๋‹ฌ๋ผ์ง„๋‹ค๊ณ  ํ•˜์˜€๋Š”๋ฐ(Rossell et al, 2009), ๋Œ€์ƒ์ง€์˜ ์‹์ƒ ๋‹ค์–‘์„ฑ์€ ๋ฏธ์„ธ์ง€ํ˜•๊ณผ ์—ฐ๊ด€์„ฑ์ด ์žˆ๋Š” ๊ฒƒ์œผ๋กœ ํŒ๋‹จ๋˜์—ˆ๋‹ค. ๊ฒฐ๊ณผ…”
unclassified
“…Thus, wetland species established in pools would be able to more easily establish on the lower portions of hummocks. Rossell et al (2009) also observed the colonization of both OBL and FACW species on drier ridge microtopography. Not all site conditions support wetland species on elevated microforms, however, as Bruland et al (2005) observed very distinct vegetation communities between microforms, in which hummocks did not support any OBL or FACW species.…”
Section: Microtopographymentioning
confidence: 69%
“…Microtopography was also a strong driver in the development of herbaceous vegetation communities. The effects of microtopography on understory species partitioning has been observed in natural communities (Beaty 1984, Paratley andFahey 1986), and increasingly has been shown to influence vegetation patterns in created wetlands (Vivian-Smith 1997, Bruland and Richardson 2005, Moser et al 2007, Rossell et al 2009, Simmons et al 2011. In this study, it was expected that most wetland species would occur in pools, and decrease in coverage with increasing elevation.…”
Section: Microtopographymentioning
confidence: 81%